2015
DOI: 10.1038/ncomms9136
|View full text |Cite|
|
Sign up to set email alerts
|

The seasonal sea-ice zone in the glacial Southern Ocean as a carbon sink

Abstract: Reduced surface–deep ocean exchange and enhanced nutrient consumption by phytoplankton in the Southern Ocean have been linked to lower glacial atmospheric CO2. However, identification of the biological and physical conditions involved and the related processes remains incomplete. Here we specify Southern Ocean surface–subsurface contrasts using a new tool, the combined oxygen and silicon isotope measurement of diatom and radiolarian opal, in combination with numerical simulations. Our data do not indicate a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 73 publications
(192 reference statements)
9
65
0
Order By: Relevance
“…Contamination, via the presence of residual tephras or clays can compromise the precision of reconstructions, with the introduction of significant isotopic offsets (Morley et al, 2005;Lamb et al, 2007;Brewer et al, 2008). This is often more pronounced for diatoms (and radiolarians; Abelmann et al, 2015) due to the ability for contaminant valve adherence and occlusion, over sponge spicules that can be picked. Clay δ 30 Si compositions are estimated between −2.95‰ and +2.5 (Douthitt, 1982;Georg et al, 2009;Opfergelt and Delmelle, 2012), which can significantly lower reported δ 30 Si diatom values [published values range between −0.07 and +3.05‰; (De La Rocha et al, 2000;Cardinal et al, 2007;Sun et al, 2013;Panizzo et al, 2014Panizzo et al, , 2016] and outside of analytical uncertainty, while high sample presence of different phases of bSiO 2 can have a similar effect (e.g., δ 30 Si sponge signatures vary between −5.72 and +0.…”
Section: Challenges For Palaeo-record Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…Contamination, via the presence of residual tephras or clays can compromise the precision of reconstructions, with the introduction of significant isotopic offsets (Morley et al, 2005;Lamb et al, 2007;Brewer et al, 2008). This is often more pronounced for diatoms (and radiolarians; Abelmann et al, 2015) due to the ability for contaminant valve adherence and occlusion, over sponge spicules that can be picked. Clay δ 30 Si compositions are estimated between −2.95‰ and +2.5 (Douthitt, 1982;Georg et al, 2009;Opfergelt and Delmelle, 2012), which can significantly lower reported δ 30 Si diatom values [published values range between −0.07 and +3.05‰; (De La Rocha et al, 2000;Cardinal et al, 2007;Sun et al, 2013;Panizzo et al, 2014Panizzo et al, , 2016] and outside of analytical uncertainty, while high sample presence of different phases of bSiO 2 can have a similar effect (e.g., δ 30 Si sponge signatures vary between −5.72 and +0.…”
Section: Challenges For Palaeo-record Interpretationmentioning
confidence: 99%
“…A recent example, used both oxygen and Si isotopes in diatoms and radiolarians, from glacial-aged sediments from the Southern Ocean, to provide reconstructions of seasonal nutrient cycling. Data show strong variability in the mixed layer depth in the seasonal sea-ice zone, which allowed for sufficient nutrient exchange between surface and deeper waters, thereby fueling carbon drawdown in an otherwise highly stratified glacial Southern Ocean (Abelmann et al, 2015). Diatom δ 30 Si and organic-bound δ 15 N archives from the Southern Ocean have also been coupled with a spicule δ 30 Si record of bottom water DSi concentrations to investigate DSi utilization across the last glacial termination.…”
Section: Multi-proxy Geochemical Approaches In Palaeoceanographymentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon transport into and within the cell is likely the basis for the fractionation of stable Si isotopes. All silicifiers investigated to date fractionate Si isotopes relative to the seawater in which they grow, but sponges have a more variable and potentially greater isotopic fractionation than either diatoms or radiolarians (de la Rocha et al, 1997;Hendry and Robinson, 2012;Hendry et al, 2014;Abelmann et al, 2015). Such isotopic fractionation may be related to the biochemical pathways involved in Si metabolism, and may reflect the organism's affinity for silicic acid and efficiency of uptake and utilization.…”
Section: Evolutionary Competition Across Geological Timementioning
confidence: 99%